2016
DOI: 10.3233/xst-160571
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib sensitizes esophageal squamous cancer cells to radiotherapy by suppressing the expression of HIF-1α and apoptosis proteins

Abstract: Radiation therapy is a typical treatment for esophageal squamous cell carcinoma (ESCC), especially middle and upper segment esophagus, and inoperable patients. However, how to promote radiation sensitivity in radio-resistant cancer cells is a conundrum. Here, our study investigated the radiosensitizing effect of bortezomib, a specific and reversible dipeptide boronic acid analog, in ESCC cells. Human esophageal squamous carcinoma cell lines Eca109 and TE-13 were exposed to hypoxia and/or ionizing radiation (IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Inhibition of HSP90, a key chaperone protein of HIF-1α, overcomes resistance to chemotherapy and radiotherapy in pancreatic cancer 125 . Bortezomib, a reversible proteasome inhibitor, sensitizes esophageal squamous cancer cells to radiotherapy by decreasing HIF-1α and VEGF expression 126 .…”
Section: Interplay Between Mitochondrial Dysfunctions and Hifsmentioning
confidence: 99%
“…Inhibition of HSP90, a key chaperone protein of HIF-1α, overcomes resistance to chemotherapy and radiotherapy in pancreatic cancer 125 . Bortezomib, a reversible proteasome inhibitor, sensitizes esophageal squamous cancer cells to radiotherapy by decreasing HIF-1α and VEGF expression 126 .…”
Section: Interplay Between Mitochondrial Dysfunctions and Hifsmentioning
confidence: 99%
“…Among the wide ranges of potential radiosensitizers investigated, well-recognized reagents includes gold nanoparticles, hypoxia-specific cytotoxins, drugs involved in DNA repair, drugs involved in cell signaling, and growth factors [8]. Experimental and preclinical studies have demonstrated the efficacy of radiosensitizers in improving response to radiation therapy, and several inhibitors have been or are currently being tested as potential radiosensitizers in clinical trials, including poly(ADP-ribose) polymerase inhibitors(PARPi) [911], proteasome inhibitors [1214], and epidermal growth factor receptor inhibitors [15]. Recently some strategies have been investigated as the radiosensitizers for osteosarcoma, histone deacetylase inhibitors (HDACi),DNA-PKcs inhibitors are considered as attractive options for the radiosensitization of this cancer type [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It regulates hypoxia-inducible factor (HIF) 1 and 2, which in turn can play critical roles in cancer metabolism, stem cell proliferation, maintaining aggressiveness and metastatic potential of both OSCC and OAC cells ( Figure 3 ) ( 119 , 120 ). Overexpression of HIFs also reduces radio-sensitivity ( 121 , 122 ) and induces EMT in cancer cells ( 123 , 124 ). On the other hand, inhibition of HIF1α resulted in suppression of tumorigenicity of OSCC cells in both in vitro and in vivo ( 125 ).…”
Section: Targeting Hypoxia-related Pathways In Esophageal Cancer To Ementioning
confidence: 99%